2019
DOI: 10.4103/1673-5374.245473
|View full text |Cite
|
Sign up to set email alerts
|

Paternal physical exercise modulates global DNA methylation status in the hippocampus of male rat offspring

Abstract: It is widely known that maternal physical exercise is able to induce beneficial improvements in offspring cognition; however, the effects of paternal exercise have not been explored in detail. The present study was designed to evaluate the impact of paternal physical exercise on memory and learning, neuroplasticity and DNA methylation levels in the hippocampus of male offspring. Adult male Wistar rats were divided into two groups: sedentary or exercised fathers. The paternal preconception exercise protocol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Furthermore, exercise-related epigenetic changes extend beyond the individuals who engage in exercise. A study in rats descended from parents that participated in a treadmill-race training protocol, 20 min daily, five days a week, for 22 days prior to mating, had a better spatial development, as well as better DNA global methylation in the hippocampus compared with sedentary rats, suggesting a link between the pre-conceptional physical exercise of their progenitors and the improvement of the cognitive capacity of their descent, possibly related with the epigenetic programming in the hippocampus [58]. For these and other reasons, it is suggested that physical exercise be carried out at all life stages, taking into consideration the capacities or even the limitations of each individual, and that physical exercise should form part of the individual’s lifestyle.…”
Section: Physical Exercise and Redox Responsementioning
confidence: 99%
“…Furthermore, exercise-related epigenetic changes extend beyond the individuals who engage in exercise. A study in rats descended from parents that participated in a treadmill-race training protocol, 20 min daily, five days a week, for 22 days prior to mating, had a better spatial development, as well as better DNA global methylation in the hippocampus compared with sedentary rats, suggesting a link between the pre-conceptional physical exercise of their progenitors and the improvement of the cognitive capacity of their descent, possibly related with the epigenetic programming in the hippocampus [58]. For these and other reasons, it is suggested that physical exercise be carried out at all life stages, taking into consideration the capacities or even the limitations of each individual, and that physical exercise should form part of the individual’s lifestyle.…”
Section: Physical Exercise and Redox Responsementioning
confidence: 99%
“…What the research literature refers to is the transgenerational transmission of the effects of paternal experiences to offspring. Nevertheless, there are also conflicting results (Yeshurun et al , 2017; Mega et al , 2018; Spindler et al , 2019; Hoffmann et al , 2020). The results of these studies showed that in some cases, paternal environmental enrichment did not positively affect cognitive behaviors and neurobiologic factors in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not use any physical exercise or enriched cages. In contrast, some conflicting studies investigated the effects of paternal high-intensity physical exercise using a treadmill (Mega et al , 2018; Spindler et al , 2019) or paternal environmental enrichment by environmentally enriched cages (Yeshurun et al , 2017; Hoffmann et al , 2020) on behavior and neurobiologic factors of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Global DNA methylation levels less than 1% are not uncommon for brain tissues. Reports of global DNA methylation in the hippocampus have ranged from >0.01% to 1.15% across rat studies using the same global quantification kit as the current study [ 18 , 19 ]. We found that half of our animals had global DNA methylation levels less than 1.15% in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%